Improving Students’ Knowledge and Engagement in Immunology Course Using Video-Based Learning and Concept Mapping in Modified E-tivities - Triastuti, Asih; Pramundita Ramadani, Arba (IJCER (International Journal of Chemistry Education Research), 2024)
E-tivities were implemented in the online class of Immunology at the Department of Pharmacy UII using video-based learning (VBL) and concept mapping exercises to enhance student motivation and knowledge. The class measurement method was used by comparing the previous academic year's lecture evaluation and outcomes (the 2021 semester without video and concept mapping) and the 2022 semester (with E-tivities using VBL and concept mapping). According to the evaluation results, the combination of learning methods with learning video and concept mapping increased the student's interest and enthusiasm for learning. Furthermore, the student's mastery of the material increased from 8% to 41%, resulting in an increase in the student's final grade. The combination of video-based learning and concept mapping increased student motivation and knowledge